Noninvasive indocyanine green plasma disappearance rate predicts early complications, graft failure or death after liver transplantation - Schneider, Lutz; Spiegel, Martin; Latanowicz, Sebastian; Weigand, Markus A.; Schmidt, Jan; Werner, Jens; Stremmel, Wolfgang; Eisenbach, Christoph (Hepatobiliary & pancreatic diseases international, 2011)
Background - Early detection of graft malfunction or postoperative complications is essential to save patients and organs after orthotopic liver transplantation (OLT). Predictive tests for graft dysfunction are needed to enable earlier implementation of organ-saving interventions following transplantation. This study was undertaken to assess the value of indocyanine green plasma disappearance rates (ICG-PDRs) for predicting postoperative complications, graft dysfunction, and patient survival following OLT. - Methods - Eighty-six patients undergoing OLT were included in this single-centre trial. ICG-PDR was assessed daily for the first 7 days following OLT. Endpoints were graft loss or death within 30 days and postoperative complications, graft loss, or death within 30 days. - Results - Postoperative complications of 31 patients included deaths (12 patients) or graft losses. ICG-PDR was significantly different in patients whose endpoints were graft loss or death beginning from day 3 and in those whose endpoints were graft-loss, death, or postoperative complications beginning from day 4 after OLT. For day 7 measurements, receiver operating characteristic curve analysis revealed an ICG-PDR cut-off for predicting death or graft loss of 9.6% per min (a sensitivity of 75.0%, a specificity of 72.6%, positive predictive value 0.35, negative predictive value 0.94). For prediction of graft loss, death, or postoperative complications, the ICG-PDR cut-off was 12.3% per min (a sensitivity of 68.9%, a specificity of 66.7%, positive predictive value 0.57, negative predictive value 0.77). - Conclusions - ICG-PDR measurements on postoperative day 7 are predictive of early patient outcomes following OLT. The added value over that of routinely determined laboratory parameters is low.